(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
The objective of this study is to explore the potential utilization of linguistic corpora in the investigation of foreign languages. The subject under investigation is the conception of establishing an English language corpus that reflects the regional and dialectical peculiarities linked to globalization. The authors delve into the process of constructing language corpora, their various types and structures, and the current trends that influence the study of the English language. Corpus linguistics provides a framework for examining the communicative use of the English language, which is predicated on extensive volumes of speech. Corpus-based research can serve as a foundation for designing curricula and composing textbooks in English, delivering lectures and specialized courses on intercultural communication, linguistic and cultural studies, cognitive linguistics, and foreign language teaching methodologies